PENGAWASAN IZIN SURAT HAK PENEMPATAN (SHP) KIOS PASAR TRADISIONAL (STUDI KASUS PASAR RUMBAI KOTA PEKNBARU) - Pitri Pebrianti; Abdul Sadad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The supervision of the placement rights letter is to assist in the implementation of Regional Regulation Number 9 of 2014 which contains that every trader must have a Right of Placement. There are still many traders who do not have these Placement Rights letters in traditional markets. By not making a Placement Rights Letter this is one of the factors that decreases market retribution. Traders still do not understand this Placement Rights Letter because the merchant feels that the SHP is just a stall rental permit. Supervision is carried out every time there are reports or data of traders entering to make stall rights letters which are included in Pekanbaru Mayor Regulation Number 30 of 2016. Research conducted using qualitative research methods. This study uses the concept of supervision by Manullang, namely: Determining a Measuring Instrument (Standard), Conducting Assessment, Conducting Corrective Action. This research data collection techniques carried out were observation, interviews, documentation and literature study using descriptive analysis techniques. Supervision of the Placement Rights Letter of traditional markets in Pekanbaru, especially the tassel market, is not in accordance with the Regional Regulation of Pekanbaru City Number 9 of 2014 and the Regulation of the Mayor of Pekanbaru Number 30 of 2016. The supervision of the Placement Rights Letter was supervised by the Disperindag by the market and assisted by the UPTD. The market sector assigns tasks to the UPTD if there are problems in the market that have not been resolved. Problems arising, especially the tassel market, among others, are many traders who do not have a Placement Rights Letter, traders are late paying kiosk rental fees, traders complain lonely buyers who come to the tassel market to shop and less safe and comfortable tassel market conditions for traders and existing buyers. The factors that influence the Supervision of Placement Rights Permit Traditional Market stall (Case Study of market Rumbai Pekanbaru City) are human resources and merchant participation. Human resources will influence supervision so that merchant participation is expected. So that payments will be made on time. Keywords: Supervision, Letter Of Placement Rights Stall, Traditional Market